A state-of-the-art review of tamoxifen as a potential therapeutic for duchenne muscular dystrophy - Botti, Valeria; Menzel, Olivier; Staedler, Davide (Frontiers in Pharmacology, 2022)
Introduction: This systematic review analyzes the state-of-art repurposing of the drug tamoxifen (TAM) in the treatment of Duchenne Muscular Dystrophy (DMD), including its mechanism of action, toxicological findings, and past and ongoing clinical trials. A parallel aim of this work was to explore whether evidence exists to support further funding of investigation on TAM treatment for DMD patients with a pivotal trial in young patients. Bringing evidence and answering the scientific question of whether this treatment could improve the quality-of-life of DMD patients is needed to establish guidelines and accelerate access to promising therapies for DMD patients. Methods: The search was conducted in January 2022 utilizing PubMed. All MeSH terms for “Duchenne Muscular Dystrophy” and “tamoxifen” were used. The inclusion and exclusion criteria were defined according to the PICOS framework. Results: The included publications all explored the use of TAM with promising outcomes in muscular strength recovery and a decrease in pathology biomarkers. Two reviews recognize TAM as a potential treatment for DMD patients and state that drug repurposing plays a crucial role in the quest for a drug candidate to treat this rare disease. Conclusion: According to available data, TAM shows promise as a treatment for DMD, both pharmacologically and clinically. However, published data to date are insufficient to definitively conclude the beneficial effect of TAM on quality-of-life and ultimately survival, particularly in the youngest patients diagnosed with DMD.